2002
DOI: 10.1152/ajpcell.00608.2001
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the M-type sPLA2 receptor on neutrophils and its role in elastase release and adhesion

Abstract: Secretory phospholipase A(2) (sPLA(2)) produces lipids that stimulate polymorphonuclear neutrophils (PMNs). With the discovery of sPLA(2) receptors (sPLA(2)-R), we hypothesize that sPLA(2) stimulates PMNs through a receptor. Scatchard analysis was used to determine the presence of a sPLA(2) ligand. Lysates were probed with an antibody to the M-type sPLA(2)-R, and the immunoreactivity was localized. PMNs were treated with active and inactive (+EGTA) sPLA(2) (1-100 units of enzyme activity/ml, types IA, IB, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 78 publications
3
61
0
6
Order By: Relevance
“…The mRNA for the M-type-R is expressed in human kidney, lung, pancreas, placenta, and skeletal muscle (25,30). Although the presence of the M-type-R has been reported in human neutrophils and monocytes (23,48), the resident cells expressing this receptor in human tissues have not been identified. We provide in this study the first demonstration that the M-type-R is expressed in HLM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNA for the M-type-R is expressed in human kidney, lung, pancreas, placenta, and skeletal muscle (25,30). Although the presence of the M-type-R has been reported in human neutrophils and monocytes (23,48), the resident cells expressing this receptor in human tissues have not been identified. We provide in this study the first demonstration that the M-type-R is expressed in HLM.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some sPLA 2 s interact with specific membrane receptors (21). In particular, it has been suggested that activation of the M-type receptor (M-type-R) may be involved in some in vitro sPLA 2 -induced effects (13,(22)(23)(24). The M-type-R is a 180-kDa protein cloned from various species, including humans (25).…”
Section: In Inflammationmentioning
confidence: 99%
“…Recently, it has been suggested that the sPLA 2 receptor is involved in elastase release and neutrophil adhesion (15). Silliman et al (15) demonstrated that human neutrophils express M-type sPLA 2 receptor by using a polyclonal Ab to the human M-type sPLA 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we demonstrated that sPLA 2 -IB stimulates CXCL8 production in human neutrophils. On the intracellular signaling pathways induced by sPLA 2 -IB, Silliman et al (15) showed that sPLA 2 -IB stimulated not ERK, but p38 kinase, which performs a crucial role in the elastase release. However, in our study, we found that ERK phosphorylation was dramatically induced by sPLA 2 -IB in human neutrophils, and ERK activity is critically involved in the sPLA 2 -IB-induced CXCL8 production in human neutrophils (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation